Keterintegrasian dan perkembangan industri pedesaan: studi kasus di dua desa di Klaten dan Gunung Kidul - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1993)
Abstract This study examines the linkages within industry and between industry and the rest of rural economy. Its impacts on the integration of economy at local level is also examined. It especially focuses on the interactions of rural sector and their effects on the development of industry. By applying growth linkages analysis the study found that the linkages between industry and other sectors are relatively weak. This conditions had hampered the development of rural industries. Keywords: industri pedesaan